Pengaruh Non Performing Loan (Npl) dan Return On Asset (ROA) Terhadap Penyaluran Kredit Lembaga Perkreditan Desa di Kecamatan Sukawati - I Made Waka Sapta Anggi Pranadhi; Kompiang Bagiada; Ni Putu Rediatni Giri (Warmadewa Economic Development Journal (WEDJ), 2021)
Lembaga Perkreditan Desa (LPD) has a very big role in the village economy, because the LPD acts as an intermediary to collect funds in the form of savings, and channel them back into credit. The purpose of this study was to determine the effect of Non Performing Loans (NPL) and Return on Assets (ROA) on LPD Credit Distribution in Sukawati District simultaneously and partially. The research method in this study uses quantitative methods while the analysis technique used is multiple linear regression analysis. The results of the analysis of this study state that the NPL and ROA simultaneously do not have a significant effect on LPD Credit Distribution in Sukawati District. Partially, NPL and ROA have no significant effect on LPD Credit Distribution in Sukawati District.